MONITORING AND EVALUATION OF THE VARIABILITY OF ORE QUALITY DURING PRODUCTION AT THE KOCH-BULAK DEPOSIT - Inogamov Ibrahim Ilkhamovich; Ashuraliev Buned Kamalidinovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article presents an analysis of scientific papers devoted to forecasting the quality indicators of ore raw materials during the development of deposits by underground method. The author analyzes the variability of the qualitative indicator in the Kochbulak mine, and based on the results of analytical calculations determines the variability of qualitative indicators and the complexity of the block by the geological factor.